Waste Processing in the Raudhatul Islamiyah Mosque Centra Java Village, Ambawang River District, Kubu Raya District - Ulli Kadaria; Ricka Aprillia; Aini Sulastri; Govira Christiadora Asbanu; Wahdaniah Muktar (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2021)
As one of the public facilities with a reasonably solid mobilization of activities, the mosque requires adequate facilities and infrastructure substantial waste. Likewise, the Raudhatul Islamiyah Mosque on the edge of the Trans Kalimantan road, Ambawang District, and Regency of Kubu Raya do not have waste management facilities and infrastructure, including trash bins. The approach taken was to provide trash bins so that waste can be accommodated according to its type and socialization and training to increase public awareness and train partners in processing organic waste produced to have economic value. The purpose of the socialization of waste management was to provide knowledge about the grouping of waste based on the types of organic and inorganic waste, how to sort waste and its utilization and increase the understanding of partners regarding how to make compost. The face-to-face method was used in lectures, discussions, questions and answers, simulations and field practice. The materials provided include classifying waste based on its type, problems caused by waste, how to sort waste and how to process organic waste into compost. In addition, training on composting was given after the socialization material was completed. The final activity was the handover of 2 segregated trash bins with a capacity of 50 litres and a composter with a capacity of 5 litres equipped with an activator that functions to accelerate the work of microorganisms in the composting process of organic waste.